Analysis of The Implementation of Good Amil Governance Based on the Zakat Core Principle and The Application of PSAK No. 109 Concerning Zakat Accounting at The Padang City National Amil Zakat Agency - Sufriandio Sufriandio; Murniati Murniati (Indonesia Banking School, 2022)
The potential for zakat in Indonesia is very large, where Indonesia is a country with the largest Muslim population in the world. In fact, according to 2018 government data, of the 217 trillion potential zakat, on-ly 4 percent or around 8 trillion has been collected. So there is still a margin of 96 percent. The large mar-gin is inseparable from a number of challenges faced in collecting zakat in Indonesia. One of the challeng-es is related to the accountability of zakat management organizations. The Good Amil Governance (GAG) system based on the Zakat Core Principle (ZCP) and the application of PSAK 109 on Zakat Accounting is a system that aims to realize the management of zakat institutions that encourage the formation of a clean, professional and transparent management work pattern. The purpose of this study is to analyze the imple-mentation of good Amil Governance based on the Zakat Core Principle and also to assess the implementa-tion of PSAK 109 on Accounting for Zakat at the National Amil Zakat Agency (BAZNAS) of Padang City. This study uses a qualitative method with a field research approach. In collecting data, the researcher used interview, observation, and documentation techniques. Analysis of the data used using the Miles and Huberman model. The results of the study concluded that BAZNAS Padang City had carried out good amil governance and the implementation of PSAK 109 on Zakat Accounting had been carried out well in this institution.